Use of People's Pedagogy in the Formation of Moral Properties of Preschool Children - Joniyeva Tursunoy Boboxon qizi. (Peerian Journals Publishing, 2022)
The formation of moral qualities of preschool children is carried out in different ways. It is expedient to form moral qualities using folk pedagogy. As a result, the formation of moral qualities becomes much easier.
Keywords: Ethical qualities; folk pedagogy; preschool children; development